THE INFLUENCE OF THE FORCE AND FLEXIBILITY IN THE BEATING OF LEGS AND ITS RELATION WITH THE TOTAL PERFORMANCE OF SWIMMERS OF 100 METERS I SWIM CRAWL (Fiep Bulletin - online, 2014)
The objective of this study was to verify the influence of the force and flexibility in the beating of legs and its relation with the performance of 100m crawl style swimmers. The 23 best swimmers in the test of 100 meters crawl style (also known as freestyle) of the State of Rio Grande do Sul (Brazil) had been selected for this study and submitted to the evaluation of flexibility, capacity of force production, beating of legs and performance of crawl style in the distance of 100m. It had been analyzed the influence of the force and flexibility in the beating of legs, and the influence of the beating of legs in the swimmers total performance. After it, the sample was divided in three groups, as the time gotten in the test of beating of legs (group I: of 1º to 8º time; group II: of 9º to 16º time; e group III: of 17º to 23º time), with the objective to verify differences among the groups in the tested  variables. The values gotten (n=23) from the correlation between plantar flexion and beating of legs had not been significant. In the sub-groups, only group "I" got significant correlation (r=0,70 - p
Keywords: swimming; flexibility; force